The dual mobility hip arthroplasty for hip fracture in Parkinson's disease - Ayman Abdelaziz Bassiony; Saleh Gameel (Open Journal of Trauma - Peertechz Publications, 2020)
Backgroud: Patients with Parkinson's disease are at increased risk for falls and associated hip fractures as a result of tremor, rigidity, and postural instability. The available literature is limited and conflicting regarding the optimal surgical treatment and risk for postoperative complications and mortality in this unique patient population. This study question the effectiveness of mobility total hip arthroplasty in Parkinson's disease patients with proximal femoral fractures. Patients and methods: Twelve patients (13 hips) with proximal femoral fracture (fracture neck of femur in 6 cases, unstable trochanteric fracture in 5 cases and failed fixation of trochanteric fracture in 2 case). Cemented dual mobility acetabular components were used in 9 patients and a cementless dual mobility acetabular components was used in 4 patient. Follow up reports on:postoperative complication rates, in-hospital mortality, length of hospital stay, discharge status, mortality rate, recovery of prefracture ambulatory ability, and return to prefracture activities of daily living. The mean age 65 years and the mean follow-up 32 months. Results: We did not encounter any case of dislocation of the prosthesis. Seven out of 13 patients returned to pre-fracture activities of daily living with the same disability stage while 5 patients had worsening in disability by 1 stage. Conclusion: Dual mobility THA in the Parkinsonean patients provides both efficacy and stability with good functional results.